The future of presence in distance learning, a speculative design approach - Carbonel, Henrietta (Proceedings of the International Conference on Networked Learning, 2024)
Face-to-face teaching remains for many teachers the golden standard in education. However, learning is always emergent, dependent on the socio-material context. Sharing a physical space is one option, but with new digital technologies, alternative assemblages can create new and exciting learning environments and experiences. Based on the community of inquiry model, I consider cognitive, social, and teaching presence as central to a valuable educational experience in higher education. The aim of this research is to look at what presence could look like in the distance university of the future. Traditional research methods, whether quantitative or qualitative, focus on what is and on linear causal effects. However, education is open, recursive, nonlinear, and new environments introduce new actors, human and material, that affect the learning and teaching. In this research, I experiment with a speculative design method to see if it can lead to opening up new possibilities and to their critical evaluation. In six speculative design workshops, teachers developed prototypes of what presence and affective closeness could look like when students and teachers were spatially and temporally distant. I present the three main categories of prototypes that answer the needs of distance teaching creating social interactions, offering feedback, or re-creating a virtual classroom. These all show how presence can be enacted at a distance, including asynchronously. From a science-based and data-driven approach to the Virtual Reality University, via a live course map and the connected coffee cup, each prototype offers a different view of education with its opportunities, but also challenges. The prototypes also highlight how difficult it is to change our perception of what presence could look like in higher education. I use Bourdieu’s concept of habitus to help explain the difficulty of moving away from the face-to-face experience, and how a revolutionary view rather than a marginal approach to change requires a return to the fundamental questions of how students learn, the purpose of education and the role of the teacher.